Blood transfusion following major orthopaedic surgery in cerebral palsy: a retrospective analysis. Issue 3 (6th September 2020) - Lu, Matthias Z. H.; Reid, Susan M.; Lundine, Kristopher; Crighton, Gemma
Abstract: Background: Progressive musculoskeletal pathology is ubiquitous among children with cerebral palsy (CP). Corrective surgery places them at risk of major blood loss and red blood cell (RBC) transfusion. Significant variability exists in uptake of perioperative patient blood management (PBM) strategies. This study aimed to examine factors contributing to RBC transfusion and assist in future development of care pathways. Methods: A retrospective review at a tertiary paediatric hospital was undertaken to identify patients with CP undergoing either primary spinal fusion or single event, multilevel surgery (SEMLS) between 2010 and 2015. Solely soft tissue procedures were excluded. Data collected included demographics, Gross Motor Function Classification System level, surgical details, perioperative PBM and transfusion rates. Univariable analysis was performed to assess contributing factors to RBC transfusion. Results: A total of 36 spinal fusion and 98 SEMLS patients were included. Preoperatively, 12% were anaemic, but only 19% had a ferritin checked. Overall, 49 patients (37%) received RBC transfusions. Intraoperative usage of tranexamic acid and cell salvage was 89% and 81%, respectively, for the spine cohort, and 22% and 3% for the SEMLS cohort. Successively higher Gross Motor Function Classification System levels, sodium valproate usage, longer surgical times, spinal fusion, pelvis instrumentation and more osteotomies were associated with RBC transfusion. Conclusion: More than one‐third of CP patients who underwent major orthopaedic surgery received RBC transfusion. As expected, the more severely affected patients undergoing longer procedures were at highest risk. Significant improvements can be made in PBM to help optimize patients for surgery and minimize the need for transfusion. Abstract : Corrective musculoskeletal surgery for cerebral palsy children places them at risk of major blood loss and red blood cell transfusion. There is significant variability in perioperative blood management and improvements can be made to improve outcomes.